UTILISATION OF UPT HEALTH SERVICES OF BANDUNG ISLAMIC UNIVERSITY BY ACADEMIC COMMUNITY - Caecielia Makaginsar; Prathama Gilang (Universitas Muhammadiyah Yogyakarta, 2022)
Bandung Islamic University participates in improving public health level by building a clinic named UPT Health Services of Bandung Islamic University. However the number of visit is still low: 2.34% by students, while by staff and lecturers: 32.32%. Patients satisfaction could influence this condition. The study aim was to analyse clinic utilisation by academic community, and to know patients satisfaction. This study was a descriptive research with a survey approach. The population was academic community of Bandung Islamic University having a medical treatment at the clinic. The samples were students (172 people), staff (51 people) and lecturers (61 people) with inclusive criteria: active students, and permanent staff and lecturers, and exclusive conditions for students on leave and for staff and lecturers on going study and on leave. This study was conducted between January 2020 and December 2020. The result showing clinic utilisation 51.74% by students, 84.31% by staff, and 67.21% by lecturers was good enough. Students (51%), staff (74.4%) and lecturers (68.3) had high satisfaction level. This was proven by revisiting clinic more than 1 time by students (31.97%), staff (78.43%) and lecturers (57.38%), because patients satisfaction gives a direct impact on patients loyalty making patients revisit health services.